Handbook of research on entrepreneurship development and opportunities in circular economy - Baporikar, Neeta (Advances in business strategy and competitive advantage., 2020)
"This book advances the understanding of entrepreneurship development, identifies the opportunities, and manages the entrepreneurship development, policies, and programs in order to further a circular economy. In addition to entrepreneurship development and entrepreneurial opportunities, the book will cover and discuss a number of other factors necessary for a successful transformation, such as entrepreneurship and innovation, entrepreneurship and change, and entrepreneurship education"--